2018
DOI: 10.1016/j.catcom.2017.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Practical (asymmetric) transfer hydrogenation of ketones catalyzed by manganese with (chiral) diamines ligands

Abstract: International audienceThe reduction of ketones with 2-propanol as reductant was achieved using an in-situ generated catalytic system based on manganese pentacarbonyl bromide, as metal precursor, and ethylenediamine as ligand. The reaction proceeds in high yield at 80 °C, in 3 h, with 0.5 mol% of catalyst. In the presence of chiral (1R,2R)-N,N′-dimethyl-1,2-diphenylethane-1,2-diamine, as the ligand, sterically hindered alcohols were produced with enantiomeric excess up to 90%. © 2017 Elsevier B.V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Am aximum TONo f6 200 was achieved with 0.01 mol %i nt-AmOH, showing that this catalyst is competitive with the best Mnbased systems for this reaction reported to date [23b-c] No reaction took place in the presence of the sole hydride complex 3,w hile catalytic activity could be restored in the presence of base,s howing its critical role in the catalytic cycle. [10,23,24] We then enlarged the synthetic scope of this catalytic transformation ( Table 1) and found that al arge variety of aryl(alkyl)ketones could be readily reduced (entries 1-18), including sterically hindered representatives (entries 2-4, 7) inaccessible using our previous Mn catalyst based on achelating phosphine-aminopyridine ligand. [10c] Interestingly,t he reaction is tolerant to aryl groups substituted with halogen atoms (F,Cl, Br,I)and CF 3 moiety (entries 9-14).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Am aximum TONo f6 200 was achieved with 0.01 mol %i nt-AmOH, showing that this catalyst is competitive with the best Mnbased systems for this reaction reported to date [23b-c] No reaction took place in the presence of the sole hydride complex 3,w hile catalytic activity could be restored in the presence of base,s howing its critical role in the catalytic cycle. [10,23,24] We then enlarged the synthetic scope of this catalytic transformation ( Table 1) and found that al arge variety of aryl(alkyl)ketones could be readily reduced (entries 1-18), including sterically hindered representatives (entries 2-4, 7) inaccessible using our previous Mn catalyst based on achelating phosphine-aminopyridine ligand. [10c] Interestingly,t he reaction is tolerant to aryl groups substituted with halogen atoms (F,Cl, Br,I)and CF 3 moiety (entries 9-14).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[10a,23] Gratifyingly,at608 8C, in toluene,inthe presence of 1.0 mol % of 2 and 2.0 mol %o fK HMDS,a cetophenone was fully reduced to 1-phenylethanol (see Table S1 for optimization details). [10,23,24] We then enlarged the synthetic scope of this catalytic transformation ( Table 1) and found that al arge variety of aryl(alkyl)ketones could be readily reduced (entries 1-18), including sterically hindered representatives (entries 2-4, 7) inaccessible using our previous Mn catalyst based on achelating phosphine-aminopyridine ligand. Am aximum TONo f6 200 was achieved with 0.01 mol %i nt-AmOH, showing that this catalyst is competitive with the best Mnbased systems for this reaction reported to date [23b-c] No reaction took place in the presence of the sole hydride complex 3,w hile catalytic activity could be restored in the presence of base,s howing its critical role in the catalytic cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Compassing our recent investigations on the application of Mn I complexes supported by bidentate ligands in hydrogenation-type catalysis, [10] we turned our attention to the use of ligand systems now associating phosphine and NHC donors.C omplex 2 was readily obtained in 86 %y ield from the corresponding phosphine-imidazolium salt [1]OTs [11] through the sequential addition of KHMDS and [Mn-(CO) 5 Br] (Scheme 2). According to IR and NMR spectroscopy,t he air stable complex 2 forms as as ingle isomer (d P 71.3 ppm (s), d C 197.7 ppm (d, 2 J PC = 17.5 Hz, C N 2 C )), presenting af acial arrangement of the three carbonyl ligands as confirmed by an XRD study (Figure 1a).…”
mentioning
confidence: 99%
“…Reducing the H 2 pressure to 30 bar had no effect on the outcome of the reaction (entry 11). Remarkably,( R,R)-1d shows an unprecedentedly high productivity in the hydrogenation of 6a (entries [12][13][14]. When the catalyst loading was diminished to 0.01 mol %, 98 %conversion of 6a was achieved and 86 % ee was observed in (R)-7a,attaining aTON of 9800 at elevated reaction temperature (60 8 8C) in prolonged reaction time (48 h; entry 14).…”
mentioning
confidence: 98%
“…[12] Several chiral Mn complexes for asymmetric transfer hydrogenation and hydroboration of ketones were also disclosed very recently. [13] Despite these efforts,t he state of the art with nonprecious metal catalysts in ketone hydrogenation is still far from satisfactory in terms of activity,selectivity,and substrate scope.Weenvisioned that this situation might be dramatically changed by judicious design of chiral earth-abundant metal catalysts containing modular chiral ligands by fine-tuning the electronic properties and steric bulk of the ligand moieties. Herein, we report the development of anew type of modular PNN ligand and the resulting Mn I complexes for the catalysis of asymmetric hydrogenation of abroad spectrum of ketones with high activities (TON up to 9800;T ON = turnover number) and good to excellent enantioselectivities (85-98 % ee).…”
mentioning
confidence: 99%